Human Circadian Systems and the Effect of its Disorders on Insulin Activity - Azimi, Ziauddin (Journal of Natural Sciences – Kabul University, 2021)
Circadian clocks regulate alternating periods of habit, physiology, and internal metabolism, enabling living organisms, especially humans, to adapt to the 24-hour cycle of the Earth. Circadian clocks control metabolic systems to obtain and consume energy during the light/dark cycle. Impaired control of the circadian system or inconsistency with the environment or behavior, such as eating at irregular intervals, changing working hours, poor sleep, and disrupting the circadian control system, increases the risk of metabolic diseases like type II diabetes. This article reviews recent evidence regarding the effects of environmental factors on metabolism and insulin sensitivity, emphasizing the physiological relationship between circadian clocks, glucose metabolism, and insulin sensitivity. In conclusion, existing studies indicate the association of circadian disorders with insulin sensitivity. However, new strategies are needed to prevent and treat diseases caused by disruptions in circadian rhythms.